Produksi Ruang Sosial Pedagang Kaki Lima di Lapangan Niti Mandala Renon Denpasar - Tirta Yamuna, Ni Nyoman; Punia, I Nengah; Sastri Mahadewi, Ni Made Anggita (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT Street Vendors (PKL) in the Renon Field often receive control from the government. This makes interest to know how PKL in producing social space, the obstacles encountered, and to know the implications of the activities of PKL in their social space. This study found that the PKL social space production at the Renon Field was formed by the process of socializing, interacting, and forming a space zone. The stronger interaction then forms power. Constraints faced by PKL in producing their social space, namely the location permit, the small number of visitors, relatively small capitalization, competition among other traders. Keywords: Street vendors (PKL), social space production